The Era of Janus Kinase Inhibitors for Inflammatory Bowel Disease Treatment - Jin-Woo Kim (MDPI AG, 2021)
For a significant proportion of patients with inflammatory bowel disease (IBD), primary non-response and secondary loss of response to treatment remain significant issues. Anti-tumor necrosis factor therapies have been licensed for use in IBD. Other disease-related pathways have been targeted as well, including the interleukin 12/23 axis and lymphocyte tracking. However, the need for parenteral administration and the associated costs of dispensing and monitoring all biologics remain a burden on healthcare systems and patients. Janus kinase inhibitors are small-molecule drugs that can be administered orally and are relatively inexpensive, thus offering an additional option for treating IBD. They have been shown to be effective in patients with ulcerative colitis (UC), but they are less effective in those with Crohn’s disease (CD). Nonetheless, given the immune-system-based mechanism of these drugs, their safety profile remains a cause for concern. This article provides an overview of Janus kinase (JAK) inhibitors and new trends in the treatment of IBD.